Kesejahteraan Psikologis Karyawan Dalam Interaksi Aktif Dengan Konsumen Pada PT. Property Group Jln. Tb Simatupang Blok B30, Medan, Sumatera Utara - Rina Octaviana; Sagala, Rikayanti (Jurnal Riset Multidisiplin Edukasi, 2025)
This activity aims to identify factors that affect employee psychological well-being in active interaction with consumers and provide strategic recommendations to improve the quality of consumer service. The results of the study indicate that employees experience stress, fatigue, and emotional distress due to intensive consumer interaction. Other factors such as work environment, organizational communication, and social support also affect employee psychological well-being. In conclusion, this report presents strategic recommendations to improve employee psychological well-being and the quality of consumer service at PT. Property Group, including: (1) stress management training, (2) improving the work environment, (3) improving organizational communication, and (4) social support programs. These recommendations are expected to help PT. Property Group improve the quality of consumer service and improve the psychological well-being of its employees.